Characterization of the Enterobacter aerogenes sample from colonization regarding CRISPR-Cas systems and comparison with infection sample (Research, Society and Development, 2023)
Enterobacter aerogenes represents a non-spore-forming, facultative anaerobic, gram-negative bacterium. It presents itself as a multiresistant microorganism that is directly related to opportunistic infections, especially in the hospital environment. This bacterium has several mechanisms to remain active, we can highlight among these, the use of the CRISPR-Cas system to immunize them from infection by mobile genetic elements. The CRISPR system (short palindromic repeats at regular intervals in cluster) is a genetic tool responsible for cleaving the double strand of DNA at specific loci through Cas endonucleases. In view of the above, the present study aimed to characterize a sample of Enterobacter aerogenes from colonization regarding the CRISPR-Cas systems and compare it with a sample of infection. When analyzing the Colonization isolate (Ea5A), 31 genes were identified that were related to the CRISPR system, among these, only 4 were associated with Cas endonucleases, numerous spacers were found in the sample. Furthermore, the comparison between the colonization and infection isolates proposed that the genes are independent of the source of bacterial isolation. The CRISPR-Cas system is a new subject, but it is already considered an important tool for genetic engineering.